The Physical, Mental, and Social Health of Middle-Aged and Older Adults Without Close Kin in Canada. (2nd December 2021) - Margolis, Rachel; Chai, Xiangnan; Verdery, Ashton M; Newmyer, Lauren
Abstract: Objectives: We examine whether adults aged 45 and older lacking a partner and children are disadvantaged in terms of physical, mental, and social aspects of health. Then we test whether the importance of family structure for these outcomes varies by age, gender, and educational attainment. Methods: We examine aging and social network modules from the Canadian General Social Survey to estimate associations between family structure and physical, mental, and social health, with the last measured as communication with relatives and friends, civic participation, and loneliness. Results: Results show that middle-aged and older adults without partners have lower levels of physical and mental health and higher levels of loneliness than those with partners. Those without partners and children (the "kinless") interact less with relatives than those who have children but not partners, but more with friends, showing some substitution. In terms of civic participation, kinless middle-aged and older adults have significantly lower odds of this type of engagement than peers with close kin. Our interaction models find some differences by age, gender, and education, which vary by the outcome. Discussion: Our results highlight some concerns about the well-being of kinless adults in Canada, especially as related to physical and mental health and two aspects of social health, loneliness, and civic participation. We find some substitution occurring, whereby middle-aged and older adults without family are interacting more with friends than comparable peers, but such substitution is marginal.